A CHEESE-COLORED CAMPER - Stilton, Geronimo; Keys, Larry; Topraska, Topika (New York : Scholastic Inc., 2005)
Geronimo travels to Ratzikistan to help his grandfather write a guide book about this remote area
Translated from the Italian
Keywords: Stilton, Geronimo (Fictitious character) -- Juvenile fiction; Mice -- Juvenile fiction; Voyages and travels -- Juvenile fiction